Hubungan Pengetahuan Masyarakat Tentang 3M Plus dengan Kejadian Penyakit Demam Berdarah Dengue (DBD) di Wilayah Kerja Puskesmas Kereng Bangkirai Kota Palangka Raya: The Relationship of Public Knowledge About 3M Plus with the Event Of Dengue Heart Fever (DHF) in Work Area of Kereng Bangkirai Community Health Center Palangka Raya City - Kharismaka Kharismaka; Rizki Muji Lestari; Dita Wasthu Prasida (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the Dengue virus which is transmitted through the bite of the Aedes Aegypti mosquito and enters the human bloodstream. One of the triggers for the transmission of DHF at this time is the lack of knowledge and actions of a person in preventing and eradicating mosquito nests. The purpose of this study was to determine the relationship between public knowledge about 3m plus and the incidence of Dengue Hemorrhagic Fever (DHF). The design of this study used an analytical survey with a cross sectional approach. The population in this study was the entire community in the working area of ​​the Kereng Bangkirai Health Center with a total sample of 42 respondents. The sampling method used is purposive sampling. The data of this study were taken using a questionnaire. After tabulating the existing data were analyzed using the Chi-Square . analysis test. The results showed that there was a relationship between public knowledge about 3m Plus and the incidence of dengue hemorrhagic fever (DHF) (P 0.000 <a 0.05). For the Community Health Center, they can increase outreach activities or programs to prevent the occurrence of DHF such as distributing abate powder, distributing pamphlets, increasing confirmation about the PSN program and providing information to the public about DHF and how to prevent it.